Leading for learning : how to transform schools into learning organizations - Schlechty, Phillip C. (San Francisco, Calif. : Jossey-Bass, 2009)
Written by acclaimed school reform advocate Phillip C. Schlechty, Leading for Learning offers educators the framework, tools, and processes they need to transform their schools from bureaucracies into dynamic learning organizations. Schlechty explains how to move beyond some of the deeply ingrained and negative conceptions of schooling that guide so much of their practice. He shows educators how they can take advantage of new learning technologies by increasing their organization's capacity to support continuous innovation."Clearly not for the fainthearted, Schlechty's engrossing appraisal of.
Includes bibliographical references
Keywords: School improvement programs -- United Sates; School management and organization -- United Sates; Educational change -- United Sates